Salvage open radical prostatectomy for recurrent prostate cancer following MRI-guided transurethral ultrasound ablation (TULSA) of the prostate: feasibility and efficacy. (3rd May 2020) - Nair, Shiva Madhwan; Stern, Noah; Dewar, Malcolm; Siddiqui, Khurram; Smith, Elliot; Gomez, Jose A.; Moussa, Madeleine; Chin, Joseph L.
Abstract: Introduction: MRI-guided transurethral ultrasound ablation (TULSA) is a novel modality for minimally invasive ablation in patients with localised prostate cancer (PCa). A multi-national Phase 1 (30 patients) and subsequent Phase 2 (115 patients) study showed TULSA to be feasible, safe and well tolerated. However, technical viability and safety of salvage prostatectomy for those who failed TULSA is unclear. Herein, we report the feasibility and morbidity of salvage radical prostatectomy (sRP) post-TULSA. Methods: Four patients with biopsy-proven residual cancer following TULSA underwent open retropubic sRP within 39 months of TULSA. Peri-and post-operative morbidity were reported. Detailed histopathologic assessment is reported. Results: Median follow-up was 43 months after sRP. Mean operating times, blood loss, and length of stay were 210 min, 866 ml, and 3.5 days, respectively. Intraoperative finding of some fibrotic reaction of endopelvic and Denonvilliers fascia was characteristic. There were no perioperative complications. Whole-mount pathology sections showed one pT2b and three pT3a, suggesting under-staging pre-TULSA. Location of disease was compatible with persistent cancer mostly in the untreated peripheral safety region. One man received an artificial urinary sphincter. All men experienced erectile dysfunction responsive to treatment. Two patients with positive surgical margins had PSA progression requiring salvage radiation, with one requiring long-term androgen deprivation therapy. Conclusions: RP is a viable and safe salvage option if TULSA fails. Technical difficulty and perioperative morbidity were negligible and attributable to minimal peri-prostatic reaction from TULSA.